Oriented nanofibrous membranes for tissue engineering applications: Electrospinning with secondary field control. (May 2016) - Walser, Jochen; Ferguson, Stephen J.
Abstract: Electrospinning is an electrical field driven method to produce polymer fibre membranes by deposition of a charged polymer jet onto a grounded collector. Fibre alignment within these mats is usually achieved by a fast collector movement, which is not feasible for all collector geometries, such as small diameter tubes or free-form moulds. The aim of this study was to evaluate the use of charged deflector plates to apply a dynamic, alternating electrical field perpendicular to the spinning direction, in order to directly control the fibre trajectory. Different field signal types, deflector plate voltages and deflection frequency ranges have been investigated. 210 poly( ɛ )caprolactone (PCL) membranes were electrospun. SEM images of each membrane were analysed using ImageJ. Main fibre diameter and orientation, as well as the degree of fibre alignment, were calculated, while a subset of the spun scaffolds were tested for their tensile properties. Higher deflector plate voltage amplitude resulted in a better fibre alignment. The best alignment was observed in a low deflection frequency range from 2 to 10 Hz. Mean main fibre direction was 87±18°, relative to the deflection axis, while fibre alignment had only a minor effect on the average fibre diameter. Young′s modulus and yield stress increased with the ratio of the parallel fibre component. The feasibility of the described method to achieve fibre alignment was demonstrated. However, the main fibre direction is not aligned with the deflection axis, but consistently perpendicular to it, which is also reflected in the tensile properties of spun samples. Graphical abstract: Highlights: Electrospinning with advanced secondary field control. Fibre alignment due to dynamic polymer jet deflection. Deflector voltage and frequency dependent degree of alignment. Main fibre direction perpendicular to deflection direction. Tensile properties reflect achieved fibre alignment.